Gastrointestinal complications of pelvic radiotherapy: are they of any importance?. Issue 8 (11th July 2005) - Andreyev, J
Abstract : Radiation induced bowel damage affects 6000 individuals annually in the UK, with a negative impact on quality of life. Our understanding of how to treat these patients is dismally lacking an evidence base. Fibrosis seems to be the unifying underlying cause for most symptoms. Progress in understanding the development and treatment of fibrosis in these patients might have important consequences for patients with other causes of fibrosis in the gastrointestinal tract